DA'WA BIL-KITAB IN THE ACTUALIZATION OF EDUCATION ETHICS THE 5.0 ERA (STUDY OF THE BOOK ADAB AD-DUNYA WA AD-DIN BY IMAM AL-MAWARDI) - Riza Anggara Putra (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
In the industrial era 5.0, more and more of our educational challenges are moral issues. One of the books that teaches moral education is the book Adab Ad-Dunya wa Ad-Din by Imam Al-Mawardi. This book examines a lot related to Morality philosophy which is very closely related to morals. Al-Mawardi tries to provide an overview of how adab, biblical preaching and philosophy become a strong foundation for education. So the author tries to analyze the extent of the dakwah bil Kitab initiated by Al-Mawardi in reviving education in the 5.0 era. This research is a library research by collecting data from various literatures. The primary literature studied was the book of Adab Ad-Dunya wa Ad-Din and added secondary literature from various books and journals. This paper provides an overview of Al-Mawardi's thoughts regarding moral education. This paper also provides an explanation of how Al-Mawardi provides solutions to the challenges of education in the 5.0 era. Finally, this paper also provides a response to the dynamics of education in the current era according to the thoughts of Imam Al-Mawardi in the book Adab Ad-Dunya Wa Ad-Din.